Comparação entre amostra clínica e comunitária de indivíduos com transtorno de acumulação - Bárbara Luciane Perdigão Stumpf (2023)
The hoarding behavior occurs in humans from childhood and can range from collecting certain objects to the clinically diagnosed condition known as Hoarding Disorder (HD). HD poses health and safety risks to individuals, primarily due to poor hygiene conditions, animal infestations, risk of falls, and serious injuries, or even death resulting from being buried under avalanches of objects and fires. Patients with HD are commonly socially isolated, and the costs of rescue and firefighting services, healthcare and social services, unemployment benefits, and disability benefits are high for society. The prevalence of HD is estimated at 2.5%. The course of the disorder is usually chronic and progressive. The average age of onset for hoarding symptoms is 17 years. Elderly individuals with HD have a high prevalence of clinical and psychiatric comorbidities. In the biopsychosocial model of HD, individuals present as predisposing vulnerability factors for the development of hoarding symptoms: genetic predisposition, structural brain factors, traumatic events, personality traits, and cognitive impairment. The first part of this study consisted of publishing a systematic literature review of the literature with the objective of to evaluating the cognitive performance of people with HD. The study showed that, except for categorization skills, the cognitive performance of people with HD does not appear to be impaired when compared to controls. Animal hoarding, which is still poorly studied, is considered a special manifestation of HD. The second part of this study consisted of the publication of a systematic review of the literature with the objective of evaluating the characteristics of animal hoarding, especially the profile of affected individuals. The study demonstrated that, in most studies, the population consisted of middle-aged women without partners, living alone in urban areas under unsanitary conditions. The chapter "Care for individuals in hoarding situation" was also published in the guide "Animals in hoarding situation: unique health strategies for handling cases". In the literature, there seem to be differences between clinical and community samples of individuals with HD, which makes it difficult to generalize study results to the entire population with HD. Based on this assumption, we compared clinical and community samples of individuals with HD. The study showed that the community sample of individuals with HD was older, had poorer insight, higher prevalence of individuals with absent insight, and lower prevalence of comorbid OCD. The only predictor that differentiated individuals from the clinical group to the community group was the presence of comorbid OCD. Our results indicate that there seem to be differences between clinical and community samples of people with HD. The presence of comorbid OCD seems to be more frequent in clinical groups compared to community samples of individuals with HD.